Transformasi Digital Lembaga Pendidikan Islam Melalui Strategi Sistem Informasi Berbasis Enterprise Architecture - st Maizah; Mohammad Irsyad Wira Saputra (Al-Abshar: Journal of Islamic Education Management, 2026)
Digital transformation in Islamic educational institutions has become a necessary strategy to address technological developments and demands for improved educational service quality. This study aims to analyze the digital transformation of Islamic educational institutions through a strategic information system based on Enterprise Architecture (EA). The approach used was qualitative, library research, reviewing relevant literature from books, scientific journals, and previous research related to management information systems, digital transformation, and Enterprise Architecture in Islamic education. The study's findings indicate that digital transformation focuses not only on the use of technology but also on comprehensive changes in governance, administrative processes, and learning systems. Management Information Systems (MIS) play a crucial role in improving the efficiency, transparency, and accountability of educational institutions. However, their implementation still faces various challenges such as limited infrastructure, human resources, costs, and resistance to change. In this context, Enterprise Architecture (EA) serves as a strategic framework capable of comprehensively integrating business processes, data, applications, and technology, resulting in a more focused, structured, and sustainable information system. Therefore, implementing an Enterprise Architecture-based information system is a crucial strategy in supporting the digital transformation of Islamic educational institutions. EA not only improves operational efficiency but also strengthens the quality of governance and institutional competitiveness in the digital era.